Molecular signature of Epstein Barr virus-positive Burkitt lymphoma and post-transplant lymphoproliferative disorder suggest different roles for Epstein Barr virus - Navari, Mohsen; Fuligni, Fabio; Laginestra, Maria A.; Etebari, Maryam; Ambrosio, Maria R.; Sapienza, Maria R.; Rossi, Maura; De Falco, Giulia; Gibellini, Davide; Tripodo, Claudio; Pileri, Stefano A.; Leoncini, Lorenzo; et al. (Frontiers in Microbiology, 2014)
Epstein Barr virus (EBV) infection is commonly associated with human cancer and, in particular, with lymphoid malignancies. Although the precise role of the virus in the pathogenesis of different lymphomas is largely unknown, it is well recognized that the expression of viral latent proteins and miRNA can contribute to its patoghenetic role. In this study, we compared the gene and miRNA expression profile of two EBV-associated aggressive B non-Hodgkin lymphomas known to be characterized by differential expression of the viral latent proteins aiming to dissect the possible different contribution of such proteins and EBV-encoded miRNAs. By applying extensive bioinformatic inferring and an experimental model, we found that EBV+ Burkitt lymphoma presented with significant over-expression of EBV-encoded miRNAs that were likely to contribute to its global molecular profile. On the other hand, EBV+ post transplant diffuse large B-cell lymphomas presented a significant enrichment in genes regulated by the viral latent proteins. Based on these different viral and cellular gene expression patterns, a clear distinction between EBV+ Burkitt lymphoma and post transplant diffuse large B-cell lymphomas was made. In this regard, the different viral and cellular expression patterns seemed to depend on each other, at least partially, and the latency type most probably played a significant role in their regulation. In conclusion, our data indicate that EBV influence over B-cell malignant clones may act through different mechanisms of transcriptional regulation and suggest that potentially different pathogenetic mechanisms may depend upon the conditions of the interaction between EBV and the host that finally determine the latency pattern.